PENGARUH KOMPLEKSITAS BAHASA TERHADAP MINAT MEMBACA SYARAT DAN KETENTUAN DI SITUS JEJARING SOSIAL - Iis Siti Salamah Azzahra; Karomah Alfisahrin; Teti Sobari (IKIP Siliwangi, 2018)
This article aims to describe the results of research on the effect of language complexity in a text term and conditions on social networking sites to the interest of its users in reading the terms and conditions themselves. The research method used is descriptive qualitative, the sample in this study is the social media users who have a minimum of primary school education with various sexes, have used social media at least one site and spread in any city in Indonesia with a minimum sample size of 25 people. The research instrument used is a questionnaire that distributed through the Google Form service. The results showed that social media users consider that the term text and conditions in a social media use complex language and not simple, it is very influential on the small interest in reading the terms and condition.